Targeted specific inhibition of bacterial and Candida species by mesoporous Ag/Sn–SnO2 composite nanoparticles: in silico and in vitro investigation. Issue 2 (5th January 2022) - Pandey, Monica; Wasnik, Kirti; Gupta, Shubhra; Singh, Monika; Patra, Sukanya; Gupta, Premshankar; Pareek, Divya; Maity, Somedutta; Tilak, Ragini; Paik, Pradip
Abstract : Mesoporous Ag/Sn–SnO2 composite nanoparticles exhibits extraordinary inhibitory properties by targeting different proteins of bacteria and Candida species which can be used to eliminate the resistance of traditional antibiotics. Abstract : Invasive bacterial and fungal infections have notably increased the burden on the health care system and especially in immune compromised patients. These invasive bacterial and fungal species mimic and interact with the host extracellular matrix and increase the adhesion and internalization into the host system. Further, increased resistance of traditional antibiotics/antifungal drugs led to the demand for other therapeutics and preventive measures. Presently, metallic nanoparticles have wide applications in health care sectors. The present study has been designed to evaluate the advantage of Ag/Sn–SnO2 composite nanoparticles over the single oxide/metallic nanoparticles. By using in silico molecular docking approaches, herein we have evaluated the effects of Ag/Sn–SnO2 nanoparticles on adhesion and invasion responsible molecular targets such as LpfD ( E. coli ), Als3 ( C. albicans ) and on virulence/resistance causing PqsR ( P. aeruginosa ), RstA (Bmfr) ( A. baumannii ), FoxA ( K. pneumonia ), Hsp90 and Cyp51 ( C. albicans ). These Ag/Sn–SnO2 nanoparticles exhibited higher antimicrobial activities, especially against the C. albicans, which are the highest ever reported results. Further, Ag/Sn–SnO2 NPs exhibited interaction with the heme proionate residues such as Lys143, His468, Tyr132, Arg381, Phe105, Gly465, Gly464, Ile471 and Ile304 by forming hydrogen bonds with the Arg 381 residue of lanosterol 1 4α-demethylase and increased the inhibition of the Candida strains. Additionally, the Ag/Sn–SnO2 nanoparticles exhibited extraordinary inhibitory properties by targeting different proteins of bacteria and Candida species followed by several molecular pathways which indicated that it can be used to eliminate the resistance to traditional antibiotics.